2021
DOI: 10.1016/j.jhtm.2020.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Work engagement and job burnout? Roles of regulatory foci, supervisors’ organizational embodiment and psychological ownership

Abstract: The study explores the impact of promotion focus/prevention focus on the work engagement/job burnout of international tourist hotel employees, and in the meantime compare the influence of promotion focus and prevention focus. Moreover, the study explores as well whether supervisors' organizational embodiment and psychological ownership serves as moderators in the relationship between promotion focus/prevention focus and work engagement/job burnout of international tourist hotel employees. Based on an analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 47 publications
0
29
0
Order By: Relevance
“…Such employees are more inclined to translate their repertoire of skill and behavioral flexibility into a harmonious passion for serving customers, as well as ongoing service improvement. Contrarily, by shielding against errors and behaviors potentially linked with risks or negative outcomes (Dai et al , 2021), prevention-focused employees may be less prone to appreciate and access opportunities to develop skill and behavioral flexibility to challenge the status quo, which may lead to a less pronounced effect of HR flexibility on their harmonious passion.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Such employees are more inclined to translate their repertoire of skill and behavioral flexibility into a harmonious passion for serving customers, as well as ongoing service improvement. Contrarily, by shielding against errors and behaviors potentially linked with risks or negative outcomes (Dai et al , 2021), prevention-focused employees may be less prone to appreciate and access opportunities to develop skill and behavioral flexibility to challenge the status quo, which may lead to a less pronounced effect of HR flexibility on their harmonious passion.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Recent research showed that psychological ownership interacts with another factor (i.e. promotion focus) in influencing work engagement (Dai et al, 2021). This indicates that there are conditions when other factors moderate the relationship between psychological ownership and work engagement.…”
Section: Literature Review Transformational Leadership and Work Engagementmentioning
confidence: 99%
“…Furthermore, engaged workers can spread a positive working atmosphere to their surroundings, including to their colleagues, management, and in general, to the organization's stakeholders. Therefore, studies on antecedents of employees work engagement is equally essential as studies on employees negative organizational behavior, such as employees burnout (Buri c & Macuka, 2018;Dai, Altinay, Zhuang, & Chen, 2021) or employees turnover intention (Pitts, Marvel, & Fernandez, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the current study proposes that this type of in-group conflict will further result in the job burnout of employees. Job burnout has always been an important issue in the hospitality industry ( Kim, et al, 2007 ; Dai et al, 2021 ). Employees with job burnout will have diminished work performance and organizational citizenship behavior, which can in turn eventually lead to behaviors that are costly to their organization ( Xu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%